Her cold justice - Dugoni, Robert (Dugoni, Robert. Keera Duggan series, 2026)
"In a quiet South Seattle neighborhood, a suspected drug smuggler and his girlfriend are murdered in their home. When a young man named Michael Westbrook is accused of the brutal double homicide, his uncle JP Harrison turns to Keera Duggan to defend him. JP is Keera's trusted investigator, and he desperately needs Keera to save his nephew against escalating odds. The evidence is circumstantial--Michael worked with one of the victims, drugs were found in his possession, and he bolted from authorities. Ruthless star prosecutor Anh Tran has gotten convictions on much less. With the testimony of two prison informants, the case looks grave. But Keera never concedes defeat. To free her client, she must dig deep before Tran crushes both of them. As the investigation gets more twisted with each new find, Keera is swept up in a mystery with far-reaching consequences. This case isn't just murder. It's looking like a conspiracy. And getting justice for Michael could be the most dangerous promise Keera has ever made"--Dust jacket flap.